Strategies of refueling, sailing speed and ship deployment of containerships in the low-carbon background. (December 2017) - Wang, Chuanxu; Chen, Junjun
Highlights: Problems of refueling, ship speed determination and ship deployment are considered. Refueling ports and amounts, ship speed and deployment number are decision variables. Proposed model is solved by transforming into a nonlinear continuous programming model. Impact of fuel price, ship tanker capacity and carbon tax rate on decision is analyzed. Abstract: To solve the problems of refueling, ship speed determination and ship deployment of containerships, based on the nonlinear relationship between ship sailing speed, fuel consumption and carbon emissions, a corresponding nonlinear mixed integer programming model is developed by taking container transportation cost, fuel consumption cost and carbon emissions cost in multiple service routes as the total cost objective function, and ship refueling ports, refueling amounts, sailing speed and ship deployment quantities in the route as decision variables. The optimal solution can be obtained by transforming the nonlinear discrete mixed integer programming model into a nonlinear continuous programming model. The proposed model is applied to an Asia-Europe service route of China Shipping (Group) Company. The results show that the optimal refueling policy, speed selection and ship deployment can be determined using the proposed model and solution method. The impact of fuel price, container transportation quantity, ship tanker capacity and carbon tax rate on ship refueling strategy, speed and deployment is investigated. Some insights obtained from example analysis are provided.